Pengaruh Kepemimpinan Berbasis Etika Terhadap Kinerja Keberlanjutan Pemasaran : Perspektif Bisnis Bertanggung Jawab - Fuji Santoso,; Ahmad Wahyudin, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2021)
The research aims to investigate the impact of ethical-based leadership on marketing sustainability performance from a responsible business perspective. Ethics-based leadership is understood as a leadership approach that embodies moral and ethical principles in decision-making and organizational interaction. Marketing sustainability performance is measured through marketing practices that consider economic, social, and environmental consequences. The study presents quantitative and qualitative approaches used, and the research design is designed as an explanatory. The cause-and-effect relationship between the four variables tested can be explained using an explanatory design that highlights the important role of ethical leadership in shaping a sustainable organizational culture, while introducing key elements of marketing sustainability. By applying empirical research methods, data is collected through surveys, and regression analysis is performed to evaluate the correlation between the variables involved. Hopefully, the results of this research can provide a deeper understanding of how ethical leadership can affect marketing sustainability performance in a responsible business context. The practical implications of these findings are expected to guide organizations in developing more sustainable leadership and marketing strategies, enabling companies not only to economic goals but also to take into account their positive impact on society and the environment. This research is expected to make a significant contribution to the development of management and marketing literature with a focus on leadership ethics and marketing sustainability.